Two female figures standing with hands in Namaskar mudra - Temples of India Project Team (Jio Institute, 2024)
In the second small panel in the hero stone, positioned just below the row depicting the hero, stand two female figures with folded hands in namaskar mudra (salutation gesture). Their upright posture is emphasized by their drapery consisting of a decorated lower garment. The female figures represent celestial damsels believed to have arrived to escort the hero to heaven.